Study on the behavior of impurity removal from lithium iron phosphate slag using the ultrasonic-assisted sulphuric acid leaching - Zhao, Ya; Wang, Yahui; Wu, Jijun; Ma, Wenhui (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Recovery of iron phosphate from the leaching slag of used lithium iron phosphate cathode materials is an important link to achieving closed-loop recovery of lithium iron phosphate, which has not yet been effectively achieved. The study used ultrasonic-assisted sulfuric acid leaching to remove impurity elements in iron phosphate to meet the requirements of battery-grade iron phosphate on the content of impurity elements. By optimizing the leaching conditions of sulfuric acid concentration of 0.2 mol∙L-1, ultrasonic acid leaching time of 30 min, ultrasonic power of 50 W, and reaction temperature of 80 ℃, the removal efficiencies of Cr, Cu, Ni, and Zn, the impurity elements in iron phosphate, were 26.09%, 83.0%, 75.9%, and 96.3%, respectively. At this time, the content of impurity elements Cr and Zn is in accordance with the standard for battery-grade iron phosphate (HG/T 4701-2021), with the content of 50ppm and 10ppm. The leaching results show that ultrasound is beneficial to the removal of impurity elements in iron phosphate in sulfuric acid solution. The results of XRD, particle size, TEM, and XPS analyses showed that the surface of the iron phosphate particles cavitated after ultrasonic acid leaching to form a large number of pores and the particles collided with the particle size became smaller, but there were no other by-products produced during the process. This process provides ideas to achieve the reuse of leaching slag (iron phosphate) and guides the recovery of metals from waste lithium iron phosphate cathode materials.